2018
DOI: 10.1111/mec.14903
|View full text |Cite
|
Sign up to set email alerts
|

Climate warming alters the structure of farmland tritrophic ecological networks and reduces crop yield

Abstract: It is unclear how sustained increases in temperature and changes in precipitation, as a result of climate change, will affect crops and their interactions with agricultural weeds, insect pests and predators, due to the difficulties in quantifying changes in such complex relationships. We simulated the combined effects of increasing temperature (by an average of 1.4°C over a growing season) and applying additional rainwater (10% of the monthly mean added weekly, 40% total) using a replicated, randomized block e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 92 publications
(153 reference statements)
0
26
1
Order By: Relevance
“…Finally, ecological entomologists will need to capitalise on the availability of new molecular methods, such as DNA metabarcoding, as well as proven methods like multiplex PCR, to study complex ecological networks (Hrček & Godfray, 2015;Evans et al, 2016;Ye et al, 2017;Derocles et al, 2018;Kitson et al, 2018). Such approaches can reveal new host-parasitoid associations in complex communities (Condon et al, 2014) and are also vital to identify facultative endosymbionts -and hence their effects -within these networks.…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, ecological entomologists will need to capitalise on the availability of new molecular methods, such as DNA metabarcoding, as well as proven methods like multiplex PCR, to study complex ecological networks (Hrček & Godfray, 2015;Evans et al, 2016;Ye et al, 2017;Derocles et al, 2018;Kitson et al, 2018). Such approaches can reveal new host-parasitoid associations in complex communities (Condon et al, 2014) and are also vital to identify facultative endosymbionts -and hence their effects -within these networks.…”
Section: Future Directionsmentioning
confidence: 99%
“…As parasitoids can be limited in the number of eggs they can lay (Heimpel & Rosenheim, 1998), they could fail to regulate host populations under global warming. Another field experiment simulating the effects of increasing temperature on plant-aphid-parasitoid network structure in wheat crops observed an aphid outbreak without change in parasitism rates (Derocles et al, 2018). The long-term effects remain unknown.…”
Section: Effect Of Global Warming On Host Immunity and Host-parasitoimentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, DNA-based approaches can be faster, more efficient and taxonomically more comprehensive, allowing the simultaneous resolution of interactions and identification of morphologically-cryptic species (Hrček and Godfray 2015). Molecular approaches to the construction of ecological networks have become increasingly common over the last decade (Clare 2014, Evans et al 2016, Derocles et al 2018, Roslin et al 2019, Evans and Kitson 2020. Although high throughput, 'next generation sequencing' (NGS) methods are now routinely used to characterise bulk samples, their use for characterising trophic interactions in food webs has proved more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature directly affects organisms' metabolic rate, for example by favouring C 4 plants (Zavaleta et al, 2003), with likely implications for entire food webs (Moya-Laraño et al, 2012). Field experiments have shown that different trophic groups will likely respond differently to increased temperature, yet consistently leading to a simplification of the food web either in agricultural fields (Derocles et al, 2018), grasslands (de Sassi et al, 2012) or in streams (O'Gorman et al, 2012). Biological invasions also have a well-demonstrated potential to disrupt local food webs.…”
Section: Patternsmentioning
confidence: 99%